2022
DOI: 10.53894/ijirss.v6i1.1114
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the economy, tax revenue and sustainable growth in Nigeria

Abstract: Economic diversification is a panacea for ensuring sustainable growth in developing countries. Studies have associated the problem of sustainable growth with the inability to broaden tax nets.  The lack of economic diversification and the inadequate optimal utilization of tax revenue have deepened infrastructural deficits and slowed Nigeria’s sustainable growth.   However, the extent to which diversification affects sustainable growth in Nigeria remains uncertain. Consequently, this study empirically examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The importance of accounting results to investors in the valuation of a company's equity is known as value relevance . A firm's taxable income serves as a proxy for the effectiveness of its tax planning, and like other accounting measures that have a significant association with equity market value (Adegbie, Ajayi, Aguguom, & Otitolaiye, 2023;Wan, Kamarudin, & Ibrahim, 2005;Yoon, Jiang, & Cui, 2023;Zhao, Tang, Zhang, & Feng, 2023), it is also relevant to value if it has a statistical association with a firm's market values or returns Kelly (2005). The value and relevance of financial accounting earnings in the United States (U.S.) have been extensively studied in the literature.…”
Section: Book-tax Differencementioning
confidence: 99%
“…The importance of accounting results to investors in the valuation of a company's equity is known as value relevance . A firm's taxable income serves as a proxy for the effectiveness of its tax planning, and like other accounting measures that have a significant association with equity market value (Adegbie, Ajayi, Aguguom, & Otitolaiye, 2023;Wan, Kamarudin, & Ibrahim, 2005;Yoon, Jiang, & Cui, 2023;Zhao, Tang, Zhang, & Feng, 2023), it is also relevant to value if it has a statistical association with a firm's market values or returns Kelly (2005). The value and relevance of financial accounting earnings in the United States (U.S.) have been extensively studied in the literature.…”
Section: Book-tax Differencementioning
confidence: 99%
“…Tax evasion and avoidance, according to Adegbie and Fakile (2011), have played a significant role in reducing revenue accruable to the Nigerian government. Tax administration will be better positioned if tax regulations and processes are simple; tax compliance costs are minimal; taxpayers have easy access to information; and taxpayers and tax authorities have mutual trust.…”
Section: Electronic Tax Paymentmentioning
confidence: 99%
“…Australia, the United Kingdom, France, India, China, Singapore, Turkey, Malaysia, Uganda, Rwanda, and Nigeria are just a few of the developed and emerging economies that have adopted the e-tax system (Ramayah, Ramoo & Amlus, 2008;Muita, 2011). Tax evasion, non-compliance, and tax authorities' coordination with taxpayers to circumvent taxpayers are among the most serious issues confronting Nigerian tax administration (Adegbie & Fakile, 2011;Odia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ogun State comes in second with an amazing IGR of N70.92 billion and a low FAA receipt of N92 billion (representing 77%). Rivers have an amazing IGR of N140 billion and a low FAA receipt of N219 billion representing 64% (Adegbie et al, 2023).…”
mentioning
confidence: 99%
“…Unfortunately, despite the huge internally generated revenue over the years by successive governments at all levels, there is no significant evidence of optimal utilization of these revenues. For Adegbie et al (2023) reported that there is evidence of high infrastructural deficits over the years, all-time high double-digit inflation, high unemployment rate, low income per capita and unprecedented high infant mortality and poor living standards in Nigeria. There had been unparalleled looting of the national treasury and fraud cases.…”
mentioning
confidence: 99%